1980
DOI: 10.1042/bj1870429
|View full text |Cite
|
Sign up to set email alerts
|

Human FAD-dependent NAD(P)H diaphorase

Abstract: A newly discovered human diaphorase, designated diaphorase-4, which accounts for a major part of the diaphorase activity of most tissues but does not occur in erythrocytes, is described. In contrast with other human diaphorases, it is dependent on FAD for activity after electrophoresis, inhibited by low concentrations of dicoumarol and shows a marked affinity for Cibacron Blue. The molecular weight was estimated to be 49000 + 1800 by gel filtration. Diaphorase-4 appears to show person-to-person quantitative va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
0

Year Published

1990
1990
2002
2002

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(37 citation statements)
references
References 11 publications
2
35
0
Order By: Relevance
“…In 1980, Edwards et al, showed that NQOl was lacking in 4% of a British population (Edwards et al, 1980). We characterized a point mutation in the BE colon carcinoma cell line that led to a loss of enzymatic activity consistent with the absence of enzymatic activity observed in the previous studies (Traver et al, 1992).…”
supporting
confidence: 53%
“…In 1980, Edwards et al, showed that NQOl was lacking in 4% of a British population (Edwards et al, 1980). We characterized a point mutation in the BE colon carcinoma cell line that led to a loss of enzymatic activity consistent with the absence of enzymatic activity observed in the previous studies (Traver et al, 1992).…”
supporting
confidence: 53%
“…In tumour tissue from patient 3, higher protein expression than activity was measured. There is little information available on substrate specificities of the different forms of NQOs; the NQO2-encoded protein is 43 amino acids shorter at the carboxy terminal end, and several authors have suggested distinct affinities of diaphorases (NQOs) for the metabolism of several substrates, including menadione (Edwards et al, 1980; Segura-Aguilar and Lind, 1987). The NQO2 cDNA-encoded protein was found to be 50-fold to 100-fold less active at reducing the menadione readily metabolized by NQOl protein (Jaiswal et al, 1990), so we cannot discard the theory that patient 3 had this isoenzyme.…”
Section: Resultsmentioning
confidence: 99%
“…The mutant allele frequency was 0.188, which is consistent with previous reports in whites and the Hardy-Weinberg formula, as well as the first report of null NQO1 activity in 4% of the British population. 20 Acute leukemia cases had the following distribution: 58% CC; 38% CT; 4% TT.…”
Section: Resultsmentioning
confidence: 99%